Adolescent Involvement in Sports Activities and Internalisation of Moral Values (Baltic Journal of Sport and Health Sciences, 2016)
Background.  Relatively  little  knowledge  is  available  to  date  about  moral  values  among  adolescents.  As participation  in  sports  activities  may  contribute  to  positive  youth  development,  this  study  aims  to  examine  the relations between adolescents’ involvement in sports activities and the internalisation of their moral values. We assessed this relationship with respect to gender as well.Methods.  The  sample  included  385  adolescents  (192  girls  and  193  boys)  between  13  to  16  years  of  age  (M age = 14.6, SD =1.11); 43.4% (n = 167) of the research participants were involved in competitive sports. The studied adolescents had participated in their respective sport for an average of 2.97 (SD = 1.12) years. The internalisation of moral values was assessed using the 24-item adolescent-report Moral Values Internalisation Questionnaire (Hardy, Padilla-Walker, & Carlo, 2008). Four forms of value regulation were assessed (external, introjected, identified and integrated). Overall value internalisation was also evaluated.Results. Significant differences were found between adolescent involvement in sports activities and external regulation (p < .05), introjected regulation (p < .01), identified regulation (p < .05) as well as integrated regulation  (p